THE INFLUENCE OF GIVING MAGGOTS (BLACK SOLDIER FLY) IN RATION TOWARDS BROILER ABDOMINAl FAT DISTRIBUTION - I K. A. P., Putra; Astawa, I P. A.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of giving maggot caterpillars in rations on slaughter weight, bearing fat, mesenteric fat, ventricular fat and broiler abdominal fat. This research was conducted for 2 months located in Nyitdah Village, Kediri District, Tabanan Regency, Bali and used a completely randomized design (CRD) with 4 treatments and 4 replications consisting of 64 broiler chickens with homogeneous body weights. The four treatments were rations without the addition of maggot as a control (P0), rations with the addition of 5% maggot (P1), rations with the addition of 10% maggot (P2), rations with the addition of 15% maggot (P3). The variables observed were slaughter weight, bearing fat, mesenteric fat, ventricular fat, and abdominal fat. The results showed that the slaughter weight of broilers in the 5% maggot (P1), 10% maggot (P2), and 15% maggot (P3) treatments were significantly (P<0.05) higher than the P0 treatment. Bearing fat and abdominal fat in the P1, P2, and P3 treatments were significantly (P<0.05) lower than the P0 treatment. Mesenteric fat in treatments P1, P2, and P3 was not significantly (P>0.05) lower than in treatment P0. Ventricular fat in the P1 treatment was significantly (P<0.05) lower than in the P0 treatment. Meanwhile, P2 and P3 were not significantly (P>0.05) lower than the P0 treatment. The addition of maggots as much as 5%, 10%, and 15% can increase the slaughter weight and reduce the fat bearing, ventricle and abdomen of broilers. Whereas the mesenteric fat obtained the same results as the control.